A COMPARISON STUDY: TEACHER, PEER AND SELF-FEEDBACK ON STUDENTS ESSAY WRITING - Imam Sudarmaji; Marlien Bunga Lifanie (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2020)
The aim of this research was to know whether there are significant affection of reduction language error in students essay writing by using peer, teacher and self-feedback and to investigate which the best one of the strategies on reduction language error in students essay writing. The 126 tenth grade students of one senior high school in Tangerang were chosen as the sample which taken by non-random using purposive sampling. This research used experimental method with three experimental groups design. Students’ test for pre-test and post-test were used by the researcher to collect the data. The hypothesis data was tested using formula of t-test. The result showed that there was a significant effect used peer, teacher and self-feedback on reduction language error in students writing essay at the tenth grade of senior high school, but teacher feedback is better strategy than peer and self-feedback. It means that the three feedback strategies in reducing language error are effective on improving students writing skill and the teacher feedback strategy is the most effective one among the other strategies